Violence in Place: Reading Violence through Kincentric Ecology - Kearney, Amanda (International Journal of Conflict and Violence (IJCV), 2018)
This article explores violence in place, with the intent to more broadly configure the notion of violence within sociological and anthropological discourse. So too it strives to expand the field of inquiry into the effects of human-induced violence on the place world, as made up of homelands, villages, communities, and ancestral realms. Throughout the discussion links are drawn between three particular forms of violence and their harmful effects on place: the physical destruction of place, the de-signification and social disordering of place identity and character, and elemental decay as ecological decline and toxicity in place. I argue that particular epistemic habits and dispositions allow for such violence to be carried out, in the pursuit of power, authority, land, and resources. Furthermore, other epistemic habits and dispositions, namely those provided for by Indigenous epistemologies, might present pathways out from unmitigated violence and towards practices of refrain and axiological return. I propose that this is achievable through a return to kincentricity, as expressed through human responsibility over rights, and recognition of place agency and sentiency as expressed through local empiricism.